2020
DOI: 10.3390/w12082097
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations in Drought and Wetness from 1965 to 2017 in China

Abstract: Drought and extreme precipitation events can have major environmental and socioeconomic impacts. Yet, how drought and wetness are changing in China in the context of climate change is still under debate. Here, the standardized precipitation evapotranspiration index (SPEI) was calculated based on high-quality and more densely distributed daily meteorological observation data from 655 stations across China during the period of 1965–2017. National and regional trends in drought and wetness and their various chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
5
7
0
Order By: Relevance
“…These results are consistent with those of previous studies (Wu et al 2017;Zhai et al 2015;Wang 2017). For example, Zeng et al (2020) used the SPEI to observe that China had experienced a signi cant wetting trend observed in the western region, the Tibetan Plateau, and eastern China from 1965 to 2017. Xu et al (2015) showed that the western part of the North China Plain and Loess Plateau experienced a signi cant drying trend using three months of SPI, RDI, and SPEI indices; this trend was mainly attributed to a signi cant decrease in precipitation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with those of previous studies (Wu et al 2017;Zhai et al 2015;Wang 2017). For example, Zeng et al (2020) used the SPEI to observe that China had experienced a signi cant wetting trend observed in the western region, the Tibetan Plateau, and eastern China from 1965 to 2017. Xu et al (2015) showed that the western part of the North China Plain and Loess Plateau experienced a signi cant drying trend using three months of SPI, RDI, and SPEI indices; this trend was mainly attributed to a signi cant decrease in precipitation.…”
Section: Discussionsupporting
confidence: 90%
“…The wetting trend mainly occurred in the west, east, and northeast of the study area, whereas the drying trend was concentrated on the Loess Plateau. These results are consistent with those of previous studies (Wu et al 2017;Zhai et al 2015;Wang 2017). For example, Zeng et al (2020) used the SPEI to observe that China had experienced a signi cant wetting trend observed in the western region, the Tibetan Plateau, and eastern China from 1965 to 2017.…”
Section: Discussionsupporting
confidence: 90%
“…Many meteorological drought indexes had been developed for quantifying drought and wetness fluctuations, including the Palmer drought severity index (PSDI) [14], standardized precipitation index (SPI) [15], China-Z index (CZI) [16], standardized precipitation evapotranspiration index (SPEI) [17], and soil wetness deficit index (SWDI) [18]. Among these indexes, SPI and SPEI are easy to obtain and widely used for drought and wetness changes and their impact on agriculture and ecological environment in many countries and regions of the world [19][20][21][22][23][24][25]. e main advantage of the SPI is that it is calculated at multi-time scales and can monitor different drought types [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In Hubei, the variation in groundwater resources was more significant. (2) The water resources in the eco-economic belt are not evenly spatially distributed; they are concentrated in Anhui, Henan, and Jiangsu, while Hubei exhibits relative water scarcity. (3) The total volume of water resources increases or decreases with the increase or decrease in annual precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Drought and extreme precipitation events can have significant environmental and socioeconomic impacts. The effects of global warming and intensified anthropogenic activity (e.g., water reservoir construction, urbanization, and deforestation) are expected to accelerate the global hydrological cycle (2,3) and thus alter the spatiotemporal patterns of precipitation. This is in turn projected to result in the increased occurrence of extreme weather events, including severe droughts or floods, in numerous regions around the globe.…”
Section: Introductionmentioning
confidence: 99%